2021
DOI: 10.2460/javma.19.08.0389
|View full text |Cite
|
Sign up to set email alerts
|

Pathology in Practice

Abstract: In collaboration with the American College of Veterinary Pathologists

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The gray brocket deer (Mazama gouazoubira) is a Latin-American cervid with a decreasing population trend, found in forests, savannas, shrubland, and wetlands (inland) in Brazil, Bolivia, Argentina, Paraguay, and Uruguay (Black-Decima and Vogliotti, 2016). There are few reports of neoplasms in this species (Lértora et al, 2014;Navas-Suárez et al, 2018;Wilson et al, 2021), with one single case of testicular germ cell neoplasm identified as a teratoma (Lértora et al, 2014). Herein we describe a case of seminoma in a cryptorchid wild-caught gray brocket deer, highlighting the anatomopathological aspects of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The gray brocket deer (Mazama gouazoubira) is a Latin-American cervid with a decreasing population trend, found in forests, savannas, shrubland, and wetlands (inland) in Brazil, Bolivia, Argentina, Paraguay, and Uruguay (Black-Decima and Vogliotti, 2016). There are few reports of neoplasms in this species (Lértora et al, 2014;Navas-Suárez et al, 2018;Wilson et al, 2021), with one single case of testicular germ cell neoplasm identified as a teratoma (Lértora et al, 2014). Herein we describe a case of seminoma in a cryptorchid wild-caught gray brocket deer, highlighting the anatomopathological aspects of this condition.…”
Section: Introductionmentioning
confidence: 99%